2013
DOI: 10.1063/1.4824041
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption-controlled growth of BiVO4 by molecular-beam epitaxy

Abstract: Single-phase epitaxial films of the monoclinic polymorph of BiVO4 were synthesized by reactive molecular-beam epitaxy under adsorption-controlled conditions. The BiVO4 films were grown on (001) yttria-stabilized cubic zirconia (YSZ) substrates. Four-circle x-ray diffraction, scanning transmission electron microscopy (STEM), and Raman spectroscopy confirm the epitaxial growth of monoclinic BiVO4 with an atomically abrupt interface and orientation relationship (001)BiVO4 ∥ (001)YSZ with [100]BiVO4 ∥ [100]YSZ. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 34 publications
6
68
1
Order By: Relevance
“…This is in agreement with those reported by Chen et al for dense polycrystalline films, 14 though we acknowledge that our indirect gap is slightly larger than theirs: ∼2.4 eV. Epitaxial BVO transitions agree well with the work of Stoughton et al 17 Photoelectrochemistry. While the morphology shown in Figure 2 is nonideal for transport measurements, nanostructured films with high surface areas are highly desirable as photoelectrodes.…”
Section: ■ Experimental Sectionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in agreement with those reported by Chen et al for dense polycrystalline films, 14 though we acknowledge that our indirect gap is slightly larger than theirs: ∼2.4 eV. Epitaxial BVO transitions agree well with the work of Stoughton et al 17 Photoelectrochemistry. While the morphology shown in Figure 2 is nonideal for transport measurements, nanostructured films with high surface areas are highly desirable as photoelectrodes.…”
Section: ■ Experimental Sectionsupporting
confidence: 94%
“…BVO powder (micron size particles) exhibits an optical band gap of ∼2.4 eV, 34 while band gaps of ∼2.5−2.6 eV have been reported for thin films. 13,17,44 Epitaxial and polycrystalline thin films had very similar light absorption Figure S6 in the Supporting Information). This is in agreement with those reported by Chen et al for dense polycrystalline films, 14 though we acknowledge that our indirect gap is slightly larger than theirs: ∼2.4 eV.…”
Section: ■ Experimental Sectionmentioning
confidence: 82%
“…Increasing the deposition time increased the absorbance in the same wavelength ranges without affecting the absorbance onset. The fundamental direct or indirect nature of the BiVO 4 bandgap is still the subject of ongoing debate. Cooper et al suggested the presence of an additional direct transition at ≈200 meV above the indirect band gap of monoclinic BiVO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…4 shows the Raman spectra of The broadening shoulder observed at lower wavelength around 355 cm À 1 indicates the symmetric deformation modes of the VO 4 3 À tetrahedron and another predominant peak observed at higher wavelength around 820 cm À 1 attributed to the stretching modes of V-O bonds [41]. The later one indicates the BiVO 4 unit cell structure distortion induced by variation of Bi 3 þ ions which may affect any one of the factors such as doping, crystallite facet, morphology variation and defect creations [51][52][53][54][55]. It clearly shows that the characteristic peak at 820 cm À 1 shifted towards lower wavelength region by increasing the calcination temperature.…”
Section: Chemical Environment Analysismentioning
confidence: 91%